The analysis and cognition of basic melodic structures: The implication-realization model - Narmour, Eugene (Chicago University of Chicago Press, 1990)
Eugene Narmour formulates a comprehensive theory of melodic syntax to explain cognitive relations between melodic tones at their most basic level. Expanding on the theories of Leonard B. Meyer, the author develops one parsimonious, scaled set of rules modeling implication and realization in all the primary parameters of music. Through an elaborate and original analytic symbology, he shows that a kind of "genetic code" governs the perception and cognition of melody. One is an automatic, "brute" system operating on stylistic primitives from the bottom up. The other constitutes a learned system of schemata impinging on style structures from the top down.The theoretical constants Narmour uses are context-free and, therefore, applicable to all styles of melody. He places considerable emphasis on the listener's cognitive performance (that is, fundamental melodic perception as opposed to acquired musical competence). He concentrates almost exclusively on low-level, note-to-note relations. The result is a highly generalized theory useful in researching all manner of psychological and music-theoretic problems concerned with the analysis and cognition of melody."In this innovative, landmark book, a distinguished music theorist draws extensively from a variety of disciplines, in particular from cognitive psychology and music theory, to develop an elegant and persuasive framework for the understanding of melody. This book should be read by all scholars with a serious interest in music."?Diana Deutsch, Editor, Music Perception